Organizational Culture Types And Knowledge Management In U.S. Manufacturing Firms - Jones, Michael Brandt; Mujtaba, Bahaudin G.; Williams, Albert; Greenwood, Regina A. (Journal of Knowledge Management Practice, 2011)
This paper examined the relationship between organizational culture and knowledge management in a manufacturing environment. The objective of this study was to determine what organizational culture type was significantly related to knowledge management in U.S. manufacturing firms. This study used the following research questions: 1) Is organizational culture related to knowledge management in U.S. manufacturing firms? 2) What organizational culture type relates to knowledge management in U.S. manufacturing firms? The findings highlighted an opportunity for many manufacturers to improve their businesses by adopting a formal knowledge management program.
Keywords: knowledge management; Organizational culture; Culture type